Female religious life and feminist movements - Rodrigues, Ana Lívia (Em Perspectiva, 2022)
In this article I look for the influence of feminist movements on female religious life, initially I describe an overview of religious life; in the sequence I comment on the female religious life since the beginning of Portuguese domination in Brazil; finally addressing the influence of feminist movements in the religious practice of Catholics, which contributed, among other things, to the emergence of Feminist Theologies and the Catholic NGO for the Right to Decide. In this text of historical approach, gender is being used as a category of analysis to understand the relationships between women and men, mainly nuns and priests and how they are built by the Catholic institution, understanding that such construction is a process, which has undergone changes in the course of your story. Power is still mostly male in our social structures and the concept of patriarchy is understood here as an organization system, where there is an unequal distribution of power, a specific case of the Catholic religious system, in which the top positions, that is, in the hierarchy, only celibate men can act.